Liver transplantation for the sequelae of intra-operative bile duct injury - de Santibañes, E (2002)
Background Intra-operative bile duct injuries (IBDI) are potentially severe complications of the treatment of benign conditions, with unpredictable long-term results. Multiple procedures are frequently needed to correct these complications. In spite of the application of these procedures, patients with severe injuries can develop irreversible liver disease. Liver transplantation (LT) is currently the only treatment available for such patients, but little information has been published concerning the results of LT. Methods Eight patients with LT for end-stage liver disease for IBDI were studied retrospectively. They had failure of multiple previous treatments and experienced recurrent episodes of cholangitis, oesophageal variceal bleeding, severe pruritus, refractory ascites and spontaneous peritonitis. Results Mean recipient hepatectomy time was of 243 minutes (range 140–295 min), the complete procedure averages 545 minutes (260–720) and intraoperative red-blood-cells consumption was 6.5 units (1–7). One patient required reoperation due to perforation of a Roux-en-Y loop, and three developed minor complications (2 wound infections, I inguinal lymphocele). One patient died due to nosocomial pneumonia (mortality rate 12.5%). One patient required retransplantation due to delayed hepatic artery thrombosis. At follow-up 75% of patients are alive with normal graft function and an excellent quality of life. Conclusions LT represents a safe curative treatment for end-stage liver disease after IBDI, albeit a major undertaking in the context of a surgical complication in the treatment of benign disease. The complications of the surgical procedure and the long-standing immunosupression impart a high cost for resolutions of these sequelae but LT represents the only long-term effective treatment for these selected patients.